ASSESSMENT OF ENVIRONMENTAL RISK OF MINING PONDS IN BUKURU, JOSSOUTH LGC OF PLATEAU STATE - David, Shidali Samuel; Jaiye, Dukiya J; Abubakar, Adamu; T, Mathew J (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
These days there is increased environmental degradation resulting from mining is caused by inappropriate and inefficient work practices and poor measures of rehabilitation. The different stages of activities in mining have their tendencies to adversely affect the environment, the immediate society, the cultural heritage of the host community and health status of miners. This study is aimed at carrying out an assessment of the environmental risk of mining ponds in Bukuru, Jos-South LGC of Plateau State which was achieved through identification and mapping out of the major mining ponds in the study area in relation to land use activities around them and laboratory analysis of water and soil samples of major ponds.